The Transition of Plumeria in Thai Society How Globalization and Consumerism Shape Local Customs - Jantarangsee, Amata (Richtmann Publishing, 2012)
In the past, Plumeria was known as Lantom in Thailand. It was prohibited for the common man to grow this flower intheir house because it was thought that it may bring sorrow and misfortune to family members. Hence, Lantom was restricted toplanting in public places. Later, the associated meaning of sorrow was lessened as the artistic and aesthetic functions ofPlumeria became prevalent. Plumeria was introduced into common places i.e. homes, gardens, spas, resorts, restaurants,coffee shops, and the flower’s meaning significantly changed as well as it was renamed Lelawadee, which means beautifulbranching pattern, in order to better align with its new functions. This paper is to explore a changing identity of Plumeria in Thaisociety based on the meaning, name, usage, and suitable planting places. The data regarding to Plumeria history and Plumeriain Thai people’s everyday life which derived from the documents and an interview with landscape architecture was analyzed viathe concepts of globalization and consumerism. The author found that the position of Plumeria was changed by global trends: aconcept of landscape and an appreciation of leisure. As an object of consumption concerning its design and style, Plumeriadisplays signs of relaxation, chic, stylishness, Thainess, and Baliness.